(untitled) (ModaPalavra e-periódico, 2024)
This article deals with a semiotic analysis of the covers of Vogue Brasil magazine, launched in the first year of the Covid-19 pandemic. The aim of this path is to analyze the meanings produced by the covers of the aforementioned fashion magazine in 2020, a time frame in which the world witnessed the most harmful effects of the pandemic. To carry out the semiotic analysis of the covers, online digital media was used. Based on the sources found, a semiotic analysis of the covers was carried out, establishing relationships between the meanings produced by them and their connection with the “spirit of the times”, that is, with the historical context in which they were produced. As a theoretical foundation, semiotic analyzes are supported by the studies of Lúcia Santaella (1983; 2010) on Semiotics; in studies by Joly (2012) and Kossoy (2019) on image and production of meaning, in addition to other research that took magazine covers as objects of analysis, such as the work of Holanda (2017). The research results point to a discreet and subtle stance taken by Vogue Brasil when dealing with the Covid-19 pandemic, by mobilizing semiotic elements on its covers that make direct reference to this global public health issue, even though the focus of that magazine is not be matters of this nature.